2015
DOI: 10.1111/jcmm.12652
|View full text |Cite
|
Sign up to set email alerts
|

New circulating biomarkers for predicting cardiovascular death in healthy population

Abstract: There is interest to analyse newer biomarkers to identify healthy individuals at risk to develop cardiovascular disease (CVD) incidents and death. To determine in healthy individuals new circulating protein biomarkers, whose systemic levels may be associated with the risk of future development of CVD incidents and death. The study was performed in 82 individuals from the Malmö Diet and Cancer study cohort, free from CVD of whom 41 developed CVD and 41 did not. Plasma proteins related to inflammation and thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In a recent study, higher plasma levels of VDBP isotopes were associated with increased risk of cardiovascular mortality, but not incident cardiovascular events 26 . However, this study was limited by low statistical power with an inclusion of only 17 cases and did not assess whether the association was independent of other vitamin D-related biomarkers.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, higher plasma levels of VDBP isotopes were associated with increased risk of cardiovascular mortality, but not incident cardiovascular events 26 . However, this study was limited by low statistical power with an inclusion of only 17 cases and did not assess whether the association was independent of other vitamin D-related biomarkers.…”
Section: Discussionmentioning
confidence: 92%
“…Xiaoping Wang found significant correlation between HSP72 (a subgroup of HSP70) and progression of esophageal SCC [32]. However, a study in paraffin-embedded biopsy specimens of SCC from various sites of oral and para-oral regions did not find changes in Hsp70 expression [33]. These different results may be related to specific characteristics of SCC that may include from the sample type to the SCC infiltration degree that may promote distinct molecular behaviors.…”
Section: Discussionmentioning
confidence: 96%
“…Protein and metabolite biomarkers of coronary artery disease [51], heart failure [52,53], and atherosclerosis [54,55] have been identified that distinguish control and diseased individuals. In one recent study, plasma protein biomarkers were associated not only with future cardiovascular events, but also with future mortality from cardiovascular disease within an 18-year follow-up time [56]. Taken together, these cardiovascular studies suggest that the abundance of differentially regulated inflammatory response proteins may be potential biomarkers of cardiovascular events.…”
Section: Proteomics and Metabolomics As Ageing Biomarkersmentioning
confidence: 99%